دراسة نتائج العلاج الجراحي لرتق المري - ناصر, محمد; رومية, دمر; صبوح, كرم (Latakia University Journal -Medical Sciences Series, 2017)
هدف البحث الى إجراء مقاربة إحصائية لحالات رتق المريء حسب نمطها وتواردها ودراسة نتائج المعالجة الجراحية واختيار الطريقة الأمثل للعلاج ومتابعة المرضى.تضمنت عينة البحث 27 وليداً قبلوا في شعبة الحواضن في مستشفيي الأسد وتشرين الجامعيين باللاذقية بتشخيص رتق مريء أو ناسور رغامي مريئي معزول وخضعوا لعمل جراحي لإصلاح هذا التشوه، من بداية شهر كانون الثاني عام 2010 ولغاية نهاية عام 2015. كان عدد الذكور 14 مريضاً، بينما عدد الإناث 13 مريضة، تم استخدام تصنيف (Gross) لرتق المريء حيث وجد النمط (C) في 21 حالة، ووجد النمط (A) لدى 4 حالاتً، والنمط (E) لدى حالتين بينما لم تشاهد أي حالة من النمطين (B) و (D). درست التظاهرات السريرية الموجودة لدى الولدان المصابين بهذا التشوه وكذلك الموجودات المخبرية والشعاعية والتشوهات المرافقة، واستخدمت الدراسة الظليلة للمري لتأكيد التشخيص عند الحاجة. أجريت مفاغرة بدئية في النمط (C) لدى 20 حالة وتفميم مري ومعدة لحالة واحدة فقط، في النمط (A) أجري تفميم مري ومعدة لدى جميع الحالات، وتم اغلاق الناسور بمدخل رقبي في جميع الحالات من النمط (E). كان معدل البقيا 70.4% واستخدام تصنيف Spitz لتقدير درجة الخطورة. شملت المضاعفات التسريب من المفاغرة بنسبة 30% وتضيق المري بنسبة 69.2%.The research aims to make a statistical approach to the cases of esophageal atresia by its types and incidence, and to study the surgical treatment outcome and choose the best method of treatment and follow up.The study included 27 newborn patients admitted in the Neonatal Intensive Care Unit at Al-Assad University Hospital and Tishreen University Hospital in Lattakia, due to diagnosis of esophageal atresia or tracheoesophageal fistula, from the beginning of January 2010 until the end of 2015. 14 of patients were males and 13 were females. Gross classification of esophageal atresia was used, type (C) was found in 21 cases, type (A) was found in 4 cases, type (E) was found in 2 cases, while type (B) and (D) were not seen. We studied The clinical symptoms in newborn patients with this malformation, radial and laboratory findings and associated malformations. We used esophageal contrast study insure the diagnosis when needed. With type (C), we did primary anastomosis in 20 cases and cervical esophagostomy with gastrostomy in only 1 case. With type (A), we did esophagostomy with gastrostomy in all cases. With type (E), we closed the fistula with cervical approach in all cases. The survival rate was 70.4%. Spitz classification was used for risk assessment. The incidence of complications included anastomotic leakage 30% and anastomotic stricture 69.2%.